DIAGNOSTIC VALUE OF GENE XPERT MTB-RIF IN TUBERCULOSIS CONTROL PRACTICE - Zh. A. Laushkina; V. A. Krasnov; A. G. Cherednichenko (Туберкулез и болезни лёгких)
The article presents the data on the use of Gene Хpert MBT-RIF testing in 122 patients. In 69 (56.6%) patients the diagnosis of tuberculosis was confirmed, and some other non-tuberculous pulmonary diseases were verified in 53 (43.4%) patients. Efficiency of tuberculous causative agent detection by Gene Xpert was compared to routine bacteriological methods. The sensitivity of this method made 63.8%, specificity made 98.1%, prognostic value of the positive result - 97.8%, prognostic value of negative result - 67.5%. Factors associated with positive results of this method are presented.